2005
DOI: 10.4049/jimmunol.174.4.2305
|View full text |Cite
|
Sign up to set email alerts
|

IL-11 Receptor α in the Pathogenesis of IL-13-Induced Inflammation and Remodeling

Abstract: IL-13 is a major stimulator of inflammation and tissue remodeling at sites of Th2 inflammation. In Th2-dominant inflammatory disorders such as asthma, IL-11 is simultaneously induced. However, the relationship(s) between IL-11 and IL-13 in these responses has not been defined, and the role(s) of IL-11 in the genesis of the tissue effects of IL-13 has not been evaluated. We hypothesized that IL-11, signaling via the IL-11Rα-gp130 receptor complex, plays a key role in IL-13-induced tissue responses. To test this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 63 publications
1
48
2
Order By: Relevance
“…A variety of lines of evidence suggests that the consequences of hyperoxia are mediated and regulated, at least in part, by the ability of 100% O 2 to induce a variety of cytokine-receptor pathways (14,(25)(26)(27)(28)(29)(30)(31). In the majority of these studies, the cytokine ligand is induced and is presumed to mediate its effects by binding to its unaltered receptor (14,(25)(26)(27)(28)(29)31).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of lines of evidence suggests that the consequences of hyperoxia are mediated and regulated, at least in part, by the ability of 100% O 2 to induce a variety of cytokine-receptor pathways (14,(25)(26)(27)(28)(29)(30)(31). In the majority of these studies, the cytokine ligand is induced and is presumed to mediate its effects by binding to its unaltered receptor (14,(25)(26)(27)(28)(29)31).…”
Section: Discussionmentioning
confidence: 99%
“…One of the fundamental research questions in deciphering the interplay of infection and asthma is: which innate pathways are deficient in asthmatic airways so an infection could prevail? Although the effects of allergic inflammation or Th2 cytokines on airway hyperreactivity and remodeling (e.g., fibrosis and mucus production) have been relatively well investigated (31)(32)(33), little is known about the role of a Th2 cytokine milieu in regulating the airway epithelial innate immune response to infections. Early observations suggested that SPLUNC1 protein decreased in the nasal lavage fluid of human subjects exposed to allergens and irritants such as cigarette smoke (34 -38).…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, we compared the expression of IL-11, IL-11R␣, and gp130 in lungs from wild-type mice and IL-13 OE transgenic mice. We simultaneously characterized the effects of a null mutation of IL-11R␣ on the tissue effects of transgenic IL-13 (43). These studies demonstrate that IL-13 is a potent stimulator of IL-11 and IL-11R␣.…”
Section: Mechanisms Of Airway Fibrosismentioning
confidence: 99%